Japanese periodical nationwide epidemiologic survey of aberrant portal hemodynamics. Issue 8 (25th April 2019) - Ohfuji, Satoko; Furuichi, Yoshihiro; Akahoshi, Tomohiko; Kage, Masayoshi; Obara, Katsutoshi; Hashizume, Makoto; Matsuura, Tomoka; Fukushima, Wakaba; Nakamura, Yosikazu
Abstract : Aim: Idiopathic portal hypertension (IPH), extrahepatic portal obstruction (EHO), and Budd–Chiari syndrome (BCS) are characterized by aberrant portal hemodynamics of unknown etiology. The aim of this study was to explore trends in the descriptive epidemiology of these diseases through periodical nationwide surveys. Methods: Nationwide epidemiologic surveys were undertaken in 1999, 2005, and 2015 using the same protocol. The survey targets were selected from all departments of gastrointestinal medicine, surgery, pediatrics, and pediatric surgery in Japan by stratified random sampling according to the number of beds. We asked each department to complete a mail‐back questionnaire on the annual numbers of patients with IPH, EHO, and BCS during the preceding year. Results: The estimated number of BCS patients increased from 280 (95% confidence interval, 200–360) in 1999 survey to 410 (300–530) in 2015 survey, whereas the number of IPH and EHO patients has remained largely unchanged during the 15 years (IPH was approximately 1000; EHO was approximately 770 in 2015 survey). The mean age at symptom onset was approximately 45 years for IPH, 30 years for EHO, and 40 years for BCS over the past 15 years. Those who described disease aggravation from the time of diagnosis accounted for approximately 10% of IPH, 15% of EHO, and 20% of BCS patients in each of the three surveys. Conclusions: In Japan, the prevalence of BCS is increasing, while those of IPH and EHO appear to be stable. Clinical characteristics, including prognoses, have remained largely unchanged in the past 15 years.